Multicriteria Methodology for the Efficient Programming of Agricultural Cultivation Activities in a Colombian Region - Dayhanna S. Vargas; Andrés C. Vélez; Christian J. Yépez; Juan J. Bravo; Juan C. Osorio (Journal of Engineering, 2023)
The potato is one of the main agricultural products in Colombia and is the second most important crop in the country. The production of this tuber represents 3.3% of the country’s agricultural gross domestic product (GDP). More than 100,000 producer families subsist on cultivation at the national level, the vast majority of which are smallholdings. However, smallholders are not able to exploit the full potential of this activity, and one of the main factors that does not allow for improving productivity is the inefficient use of land in agricultural activities. This leads to issues such as erosion, overexploitation of soil resources, reduced productivity, and, depending on the time of year, even an excess of potato supply. Therefore, a multicriteria methodology is proposed based on the key elements of the potato crop production cycle and its environment, made up of farmers from the municipality of Ventaquemada, located in Boyacá, where potato cultivation is a traditional practice. This department is the second-largest potato-producing department in the country. A review of the literature was carried out to determine and characterise the area of the selected department, and based on the above, the relevant criteria were defined and the alternatives to be evaluated were identified. Second, the proposed model is evaluated with its respective prioritisation process of both the criteria and the alternatives according to the analytic hierarchy process (AHP) methodology. Finally, the results of the model are presented, prioritizing the type of tillage, irrigation method, seed type, and its disinfection process for potato cultivation. This takes into account topographic and climatic conditions, the ecosystem, soil type, implementation costs, among other factors specific to the case study.